v-Faculty / Leong Kee Foo - Leong , Kee Foo (2001)
The technology of graphics is moving to the era of three dimensions (30). In 1970s, people were using the text-based computer system. When the technique of 2D image processing was invented, people changed their system into 2D representation because of its ability to explain more information in only one image. Around 1990s 3D graphics have been pushed out to the market. Soon, people accepted 3D as an advance information representation medium. The most important achievement of 3D technology is the making of virtual reality, which provides human unlimited space and interactivity. The v- Faculty applies the concept of virtual reality by creating a 3D-like virtual faculty on the web. It emphasizes on user interactivity where people can communicate with the objects inside the virtual world. In the other word, a realistic-looking faculty i presented on the computer screen. Besides that, the virtual faculty provides a new online course registration system because the current system is imperfect. The current system is using a centralized processing system. It encounters the problems of data storage management and processing time. Therefore, the new system could improve these weaknesses by distributing data to the database in every faculty. In addition, the new system also provides the students with the facilities of personal data checking and examination result checking as well as courses taken checking. The research incorporates all feature mentioned above as one system, which is named v-Faculty. The detail about this research is covered in this report.